Working multisectorally in nutrition: Principles, practices, and case studies - Garrett, James; Natalicchio, Marcela; Bassett, Lucy; Levinson, James (International Food Policy Research Institute, 2011)
Improving nutrition in developing nations is likely to require a multisectoral approach that involves a variety of ministries and organizations addressing particular aspects of the problem. Despite the promise of such multisectoral efforts, relatively little research has been done on how such efforts can be made effective. Working Multisectorally in Nutrition: Principles, Practices, and Case Studies provides much-needed evidence on this topic. Using case studies from Senegal and Colombia of successful multisectoral efforts to integrate action on nutrition, the book identifies common characteristics that likely contributed to the programs’ achievements. Key factors were inspiration and support from political leaders and technical staff; effective management approaches combined with operational flexibility; and processes that brought together a wide range of stakeholders and partners to share a common vision and provide them with a clear sense of how the benefits of participation would outweigh the costs. The history of these two programs suggests that addressing complex social problems such as malnutrition often requires going beyond a single, sector-bound agency and that the resulting multisectoral efforts need a strategy for action reflective of partner needs, conditions, and context. The lessons offered in this book can be used to inform and orient policymakers, practitioners, and advocates involved in multisectoral work, not only in combating malnutrition but also, more broadly, in engaging in cross-sectoral and interagency endeavors as a whole.